2008
DOI: 10.1007/s00134-008-1130-8
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal polarization spectroscopy to detect mesenteric hypoperfusion

Abstract: Objective: Orthogonal polarization spectral (OPS) imaging is used to assess mucosal microcirculation. We tested sensitivity and variability of OPS in the assessment of mesenteric blood flow (Q sma ) reduction. Setting: University Animal Laboratory. Interventions: In eight pigs, Q sma was reduced in steps of 15% from baseline; five animals served as controls. Jejunal mucosal microcirculatory blood flow was recorded with OPS and laser Doppler flowmetry at each step. OPS data from each period were collected and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Secondly, our data do not deal with the potential influence of intra-observer variability. Although a substantial variability has been reported in the jejunal mucosal microcirculation of pigs [ 29 ], multiple studies have confirmed the excellent reproducibility in the human sublingual area [ 4 , 5 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, our data do not deal with the potential influence of intra-observer variability. Although a substantial variability has been reported in the jejunal mucosal microcirculation of pigs [ 29 ], multiple studies have confirmed the excellent reproducibility in the human sublingual area [ 4 , 5 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This criticism is based on the fact that these devices have poor reproducibility and image quality [58,59] and require time-consuming off-line analysis of the acquired images. These devices also suffer from pressure artifacts imposed by the weight of the devices [56,57] and from an inability to implement automatic analysis software to process the generated images [60].…”
Section: Cell Function Monitoringmentioning
confidence: 99%
“…Several measurements can be obtained from these images (24) , including functional capillary density (density of perfused capillaries), total vessel density, and a semi-quantitative estimation of the flow patterns. Although semi-quantitative, these scores have a good reproducibility for flow estimation through different sites (12)(13)(14)(25)(26)(27) , with good agreement of flow measurements with software in experimental conditions (28) , even though the analysis may sometimes be more complex in the gut (29) . Some software for image analysis are currently available, but the technical procedure is somewhat still semiautomatic and allows only measurements of flows lower than 1 mm/sec.…”
Section: How To Evaluate Microcirculation At the Bedsidementioning
confidence: 99%